Regimes Simplificados (II Parte) - Aguiar, Nina (2009)
In this paper, the authors analyze simplified schemes of income taxation in Italy, Germany, France and the USA. For each case, the analysis focuses on whether the tax base, by means of the simplified taxation scheme, is still formed by real income or by some other economic fact, which can work as an income proxy for taxation purposes but is not income. As simplified schemes of income taxation often consist in simplified forms of accounting for small and medium businesses, these are also analyzed and briefly compared. The authors’ main purpose is to stress the differences between simplified systems in which small taxpayers are taxed on deemed income and simplified systems in which small taxpayers are taxed on real income but are allowed to calculate their real income through a simplified method of accounting, either in its formal or substantive aspects.